On the Incentive Mechanisms for Commercial Edge Caching in 5G Wireless Networks; IEEE Wireless Communications; Vol. 25, iss. 3 - Liu Tingting; Li Dzhun; Shu Feng; Guan Haibing; Yan Shihao; Dzhayakodi Arachshiladzh D. N. K. Dushanta Nalin Kumara (2018, 2018)
Title screen